A mixed-mode examination of the teaching of lead climbing by adventure sports coaches in the UK. (2nd September 2020) - Collins, Loel; Collins, Dave
ABSTRACT: Background: We present a unique study of adventure sports coaches teaching lead climbing. Expanding existing work on judgement and decision making, we examine the coaching process and the decision making employed to manage the pedagogical and security needs of climbers when they are being introduced to lead climbing. Research design and data collection: As part of a mixed approach, an Applied Cognitive Task Analysis was initially conducted on a small sample of expert coaches ( n = 7) before a questionnaire was designed and administered with a larger sample ( n = 53). Findings: The study identifies that the tuition of lead climbing is built on nine core elements that form a shared mental model which in turn is individualised to meet the needs and demands of the individual learning to lead climb. The existence of this coherent shared mental model displays minor modifications to reflect the coach's own climbing background. More importantly, the existence of this shared mental model is derived from the instructors' own experiences of climbing and teaching lead climbing rather than any formalised training. In short, this model is actualised through an informal community of practice. Conclusion: The implication for training instructors is that the skills of adapting these nine core aspects to meet individual needs should also be given due consideration alongside the technical skills of rope work and security.